Application of Ozonated Olive Oil as Adjunctive Therapy after Periodontal Pocket Curettage towards Collagen Density of Alveolar Bone in Periodontitis Healing Process (In Vivo Study with Sprague dawley) - Dahlia Herawati; Etty Cahya Pertiwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Periodontitis is an inflammatory disease of the supporting tissue of the teeth caused by specific microorganisms or groups of specific microorganisms, resulting in progressive destruction of the periodontal ligament and alveolar bone with periodontal pocket formation. Application of ozonated olive oil in dentistry is based on the actions such as antimicrobial and therapeutic agent, needed as adjunctive therapy after periodontal pocket curretage. Collagen is the main constituent of alveolar bone extracellular matrix and needed as a scaffold in the formation of mineralized matrix. The aim of this study was to determine the density of collagen in alveolar bone on periodontitis healing process after adjunctive topical application of ozonated olive oil in periodontal pocket curretage. In this study, 32 Sprague dawley rats were randomly divided into two groups: curetted-topical application of ozonated olive oil as treatment groups and curetted-topical application of 1% CMC-Na as placebo group. Periodontitis induced by placing silk-ligature around submandibular incisors for 7 days. Subsequently, the rats were sacrificed on days 3, 5, 7, and 14 after curetted and topical application, and each group was represented by four rats. The staining was done using Mallory staining method. All the results were statistically analyzed using Kruskal-Wallis and Mann-Whitney tests. The results showed that there were significant differences (p<0,05) in the density of collagen between two groups. The study concluded that adjunctive topical application of ozonated olive oil after periodontal pocket curretage significantly increase the density of collagen in alveolar bone on periodontitis healing process in Spraque dawley.